Epigenome-Wide Association Study Reveals Differential Methylation Sites and Association of Gene Expression Regulation with Ischemic Moyamoya Disease in Adults. (24th March 2022) - He, Shihao; Ye, Xun; Duan, Ran; Zhao, Yahui; Wei, Yanchang; Wang, Yanru; Liu, Ziqi; Hao, Xiaokuan; Chen, Xiaolin; Hao, Qiang; Wang, Hao; Zhao, Yuanli; et al.
Abstract : Background . The association of DNA methylation with the pathogenesis of adult ischemic moyamoya disease (MMD) is unknown. Here, we investigated the genome-wide DNA methylation profiles in patients with MMD and identified the genes related to the pathogenesis of MMD. Methods . Whole blood samples were collected from 20 individuals, including 10 patients with ischemic moyamoya disease without any underlying disease and 10 healthy individuals. Genome-wide DNA methylation analysis was performed using Illumina 850K microarrays. Transcriptional correlation was verified using quantitative reverse transcription-polymerase chain reaction. In vitro experiments were used to analyze the association of functional defects with candidate epigenetic markers. Results . The genome-wide methylation level in the whole blood of adults with ischemic MMD was higher than that in the healthy individuals. In total, 759 methylation probes differed significantly between the case and control. The hypermethylated regions were mostly concentrated in the gene spacer regions. Among genes with the highest degree of the differential expression, KCNMA1 and GALNT2 were upregulated, whereas SOX6 and RBM33 were downregulated. Conclusions . This is the first study showing that the low expression of genes associated with epigenetic regulation, such as SOX6 and RBM33, may be related to vascular occlusion in MMD, whereas the overexpression of KCNMA1 and GALNT2 may be related to the vascular hyperplasia. The results suggest that DNA methylation was involved in the pathogenesis of MMD, and new pathogenic genes were proposed as biological markers.